2015
DOI: 10.3126/jpahs.v2i2.20326
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neonatal care practices in rural Nepal

Abstract: Introductions:Child health indicators of under-five and infant mortality has improved in Nepal, but neonatal mortality remains high. The aim of this study is to assess neonatal care practices among mothers in rural Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…As regards breast feeding, majority (92.20%) of mothers feed colostrum to their babies, which is supported by others studies [14,6], which identified just 9% and 5% women discarded colostrum prior to initiating breastfeeding respectively. In this study, more than four fifth (83.87%) of the women followed criteria of exclusive breastfeeding, which is higher than national level of Nepal [17], it was because of almost all of the women were homemaker so that they have time for exclusive breastfeeding to their baby.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As regards breast feeding, majority (92.20%) of mothers feed colostrum to their babies, which is supported by others studies [14,6], which identified just 9% and 5% women discarded colostrum prior to initiating breastfeeding respectively. In this study, more than four fifth (83.87%) of the women followed criteria of exclusive breastfeeding, which is higher than national level of Nepal [17], it was because of almost all of the women were homemaker so that they have time for exclusive breastfeeding to their baby.…”
Section: Discussionsupporting
confidence: 58%
“…Report of MoHP showed that 44% home birth in Nepal [13]; likewise another study of rural Nepal found out 45.3% home birth [14]. Similarly, in rural Bangladesh, almost all (93.7%) had delivered by unskilled persons [6].…”
Section: Discussionmentioning
confidence: 90%